2021
DOI: 10.48550/arxiv.2109.08117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lone pair driven anisotropy in antimony chalcogenide semiconductors

Xinwei Wang,
Zhenzhu Li,
Seán R. Kavanagh
et al.

Abstract: Antimony sulfide (Sb 2 S 3 ) and selenide (Sb 2 Se 3 ) have emerged as promising earth-abundant alternatives among thin-film photovoltaic compounds. A distinguishing feature of these materials is their anisotropic crystal structures, which are composed of quasi-one-dimensional (1D) [Sb 4 X 6 ] n ribbons. The interaction between ribbons has been reported to be van der Waals (vdW) in nature and Sb 2 X 3 are thus commonly classified in the literature as 1D semiconductors. However, based on first-principles calcul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Another example in chalcogenides are the well-known Sb 2 S 3 and Sb 2 Se 3 semiconductors, which were also theoretically studied for lone pair-related anisotropic effects (effective masses and mobility) to provide guidelines for using their features to design efficient solar cells devices. 57 Similar effects were also observed for Sb-based compounds, 61 19 and a Bi-based compound with a 6s 2 stereoactive lone pair. 62 To quantify this stereochemical activity, a universal method described by Hu et al 63,64 was adopted to calculate the ratio of the stereochemical activity R SCA , which involves integrating the PDOS of Sb states from a specified energy level (the point where the intensity of Sb s and Sb p is equivalent) to the Fermi level (set at 0).…”
Section: ■ Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Another example in chalcogenides are the well-known Sb 2 S 3 and Sb 2 Se 3 semiconductors, which were also theoretically studied for lone pair-related anisotropic effects (effective masses and mobility) to provide guidelines for using their features to design efficient solar cells devices. 57 Similar effects were also observed for Sb-based compounds, 61 19 and a Bi-based compound with a 6s 2 stereoactive lone pair. 62 To quantify this stereochemical activity, a universal method described by Hu et al 63,64 was adopted to calculate the ratio of the stereochemical activity R SCA , which involves integrating the PDOS of Sb states from a specified energy level (the point where the intensity of Sb s and Sb p is equivalent) to the Fermi level (set at 0).…”
Section: ■ Resultssupporting
confidence: 65%
“…Recently, theoretical studies have been reported for reduced main group cations (in oxides), such as the lone pair cation Sn 2+ (discussed later, ref ), where the high mobility of the charge carriers is mostly related to the lone pair states and the overlap between the s orbital of the lone pair cation and the anions states. Another example in chalcogenides are the well-known Sb 2 S 3 and Sb 2 Se 3 semiconductors, which were also theoretically studied for lone pair-related anisotropic effects (effective masses and mobility) to provide guidelines for using their features to design efficient solar cells devices . Similar effects were also observed for Sb-based compounds, such as Sr 6 Cd 2 Sb 6 S 7 O 10 and Sr 6 Cd 2 Sb 6 Se 7 O 10 , and a Bi-based compound with a 6s 2 stereoactive lone pair …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Bi, Sb and Sn-based materials), 1,40 low crystal symmetry (e.g. Sb 2 X 3 ) 41,42 and/or compositional complexity (e.g. multinary compounds such as CZTS and double perovskites) [43][44][45] are likely to manifest local minima on defect energy surfaces.…”
Section: Capture Into Metastable Defectsmentioning
confidence: 99%